Fiscal federalism in Germany: Stabilization and redistribution before and after unification - Ralf Hepp; Jürgen von Hagen (Rheinische Friedrich-Wilhelms-Universität Bonn, Zentrum für Europäische Integrationsforschung (ZEI), 2009)
We provide empirical estimates of the risk-sharing and redistributive properties of the German federal from 1970 until 2006, with special attention to the effects of German fiscal system base unification. We find that tax revenue sharing between the states and the federal government and the fiscal equalization mechanism (Länderfinanzausgleich) together reduce differences in per-capita state incomes by 36.9 percent during period 1970 to 1994. After the full integration of East German states into the mechanism in 1995, the redistributive effects increase slightly to about 38.6 percent. With respect to the insurance effect of the German fiscal system, our results indicate that the federal fiscal system offsets 47 percent of an asymmetric shock to state per-capita incomes. This effect has significantly decreased after the inclusion of the East German states in 1995. Furthermore, we find that the German fiscal system provides almost perfect insurance for state government budgets against asymmetric revenue shocks; also, its redistributive effect with regard to the tax resources available to state governments is very strong.
Keywords: H77; E63; F42; 330; Regional Risk-sharing; Fiscal Federalism; Monetary Union